1989
DOI: 10.1007/bf00850220
|View full text |Cite
|
Sign up to set email alerts
|

Feeding disorders and gastroesophageal reflux in infants with chronic renal failure

Abstract: Twenty-two infants (mean age 7.5 months) with chronic renal failure (CRF) were studied for their nutrition, growth, and upper gastrointestinal function. Most infants had a history of poor caloric intake and 7 had received supplemental feeding (SF) prior to the investigation. All infants were undergrown, underweight, and malnourished. The infants were characterized as having only a fair interest in food, refusing feedings, and vomiting excessively. Sixteen of 22 infants (73%) had significant gastroesophageal (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 26 publications
0
23
2
Order By: Relevance
“…These findings confirm the observations of Ruley et al, who found GOR in 16/22 (73%) infants with CRF and feeding problems. 8 In this study, however, GOR was not the only cause of vomiting and abnormalities of gastric motor activity were as common. There have been no previous studies of gastric motor function in children with CRF, but studies in adults with CRF have yielded contradictory results.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…These findings confirm the observations of Ruley et al, who found GOR in 16/22 (73%) infants with CRF and feeding problems. 8 In this study, however, GOR was not the only cause of vomiting and abnormalities of gastric motor activity were as common. There have been no previous studies of gastric motor function in children with CRF, but studies in adults with CRF have yielded contradictory results.…”
Section: Discussioncontrasting
confidence: 50%
“…We studied oesophageal and gastric motor function in 12 children (age 7 months-6-8 years) with severe CRF not undergoing dialysis who had persistent anorexia and vomiting. Eight of 12 patients had significant gastro-oesophageal reflux (reflux index 5-2% to 21-9%, mean 11-3%; controls <5%), 7/10 had altered gastric half emptying times (TY2) for 5% glucose or milk (glucose meal-controls: [8][9][10][11][12][13][14] min, two CRF patients: 18-25 min; milk meal-controls: 48-72 min, five CRF patients 27,28,82,83, and 110 min). Gastric antral electrical control activity was abnormal in 6/11 patients, with different types ofgastric dysrhythmias whereas the remainder and controls showed a regular dominant frequency of 0 05 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates that tube feeding is typically necessary for young children with CKD, especially on dialysis, who require the support supplemental tube feeding provides. Gastrointestinal reflux is significant for children with CKD with severe occurrence 73% of the time (21), and up to a third of the feed may be lost to emesis (22). The need to compensate for these losses also supports use of supplemental enteral feeding in children with CKD.…”
Section: Impact Of Nutrition On Growth In Ckdmentioning
confidence: 99%
“…Volume restrictions may also be necessary to manage other physiologic factors. Children with CKD commonly have delayed gastric emptying or frequent emesis, spitting or gastroesophageal reflux (2, 21). Some children may have emesis or discomfort because they are on peritoneal dialysis and have large dextrose based “dwells” –the term used when peritoneal dialysis fluid is equilibrating in the body, removing toxins.…”
Section: Unique Adjustments To Enteral Feedingsmentioning
confidence: 99%
“…Compounding the problem is a high rate of poor gastrointestinal motility and gastroesophageal reflux, which can lead to the loss of up to a third of feeding via vomiting. 15,[57][58][59] Thus, the need to allow feeding to be provided over extended periods of time (eg, nocturnal drip feeds) mandates the use of tube feedings. Not surprisingly, the institution of tube feeding also can help alleviate the intolerable stress placed on families in which sufficient oral intake cannot be achieved and growth suffers.…”
Section: Growth and Nutritionmentioning
confidence: 99%